Returning life to the center of Tehran: The Oudlajan foodscape - Hakimian, Shiva; Afshar, Ali; Kowalczyk-Anioł, Joanna (Turyzm/Tourism, 2019)
The Oudlajan revitalization project proposed in the article, relates to both its contemporary needs and its potential. In its idea, the project uses the Iranian tradition of ‘hangout’ and refers to current trends in spending leisure time as well as shaping (designing) inclusive urban space. In terms of purpose, the project presented is applied, and in terms of methods used, it is a descriptive and analytical (qualitative) study. The article is also a voice in the debate on tourism and urban regeneration. By displaying Persian conditions in shaping the foodscape (tourism taste-space), it contributes to the dynamically-developing research on food tourism and urban culinary space.